Keanekaragaman Jenis Capung di Kawasan Setu Cileunca Kabupaten Bandung Provinsi Jawa Barat - Insan Kurnia; Anjar Malik Hidayat; Ervina Asti Ningrum; Jelika Restiana Suherman; Dea Amanda Putri; Hadi Guna Erwahyudi (Institut Agama Islam Negeri Kerinci, 2024)
Dragonflies (and damselfly) are closely related to ecosystems, both aquatic and terrestrial. Dragonflies act as predators when they are nympha and adults, so they are often used as bioindicators of environmental quality. Setu Cileunca is an artificial reservoir built in 1857 with the main function for electricity generation. This research aims to analyze the dragonfly diversity in Setu Cileunca, West Java. The research was carried out in June 2023 in five habitat types including setu, pine forests, cultivated area, rivers and settlements. Dragonfly data was taken using a 100x20 meter strip method. Quantitative analysis was carried out using (1) chi-square test, (2) diversity index (H'), (3) evenness index (E), and (4) similarity index (IS). There were 19 species of dragonflies found from two sub-orders and six families. The most common species are found in cultivated areas (17 species) while the least common are in pine forest (4 species). The number of individuals found ranged from four individuals (pine forest) to 252 individuals (cultivated area). The chi-square test showed significantly different values ​​for both of number of species and number of individuals. The H' value for all locations is 2.48 and the E value is 0.84. The IS values ​​ranged from 0.17-0.88.